HUBUNGAN KOMUNIKASI TERAPEUTIK DENGAN INTENSITAS NYERI PADA PERSALINAN KALA I DI BPM â€œBâ€ BUKITTINGGI TAHUN 2015 - Putra, Yuhendri; Rahayu, Rahayu (Jurnal Kesehatan - STIKes Prima Nusantara, 2017)
Childbirth period (puerperium) is the reproductive period of the reproductive organ as it was before pregnancy within six weeks after birthing. In a developing country like Indonesia, the childbirth period is a critical period for the mother. It is estimated that 60% of maternal deaths of an accident after birthing within the first 24 hours with almost 50% totally. One of the psychological disorders experienced by the puerperal mother is anxiety than 20% of postpartum women experience a feeling disorder with anxiety and panic symptoms. Facial Loving Touch is one of the complementary therapies to reduce stress and anxiety. This study aims to see the effect of facial loving touch on the decrease of anxiety in postpartum mother at the Mother and Child Hospital Sayang Ibu of Pariaman in 2017. This research uses a Quasi-Experiments design with one group pretest-posttest. The time of the research from 29 August - 1 October at Maternal and Child Hospital Sayang Ibu of Pariaman. the Number of sample 10 people with sampling technique of purposive sampling. The results showed that pretest anxiety level 19.50 and posttest 15.20 Statistical test results using paired T-test obtained p = 0,0001 ≤ α 0.05 so it can be concluded that there is influence facial loving touch on decrease anxiety in postpartum at the Hospital of Mother and Child sayang ibu Pariaman in 2017. The results of this study are expected to postpartum mothers to be able to access info about the benefits of facial loving touch as one of the complementary therapies.